Investigação da influência da aplicação de óleos vegetais comestíveis como fluido de corte no processo de furação do aço ABNT 1045 - Neves, Tiago do Espírito Santo Baldez (2013)
In machining processes, cutting fluids when properly chosen and applied, may reflect benefits for the manufacture of parts and components. The fluid properties are essential so that it facilitates the machining process and reach as close as possible to the cutting edge, lubricating the chip/tool interface. The fluid can be a major problem for the environment and health of the operator. For this reason, several scientific and technological studies are constantly developed to investigate the performance and environmentally friendly alternative to machining operations. This work studies the effect of vegetable oils (sunflower, canola, soybean, corn and babassu) as cutting fluids applied as MQF - minimal amount of fluid in the machining forces for the drilling process of ABNT 1045 carbon steel, compared with application of fluid in abundance (overhead cooling), dry machining and commercial oil LB2000 as MQF, for different cutting conditions. It was studied the effect of cutting speed, feed rate and length of the hole. At lower feed rates the best results were obtained with canola oil followed by sunflower at higher feed rates.